2010
DOI: 10.1007/s11427-010-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclin Y in non-small cell lung cancer is associated with cancer cell proliferation

Abstract: Cyclin Y (CCNY) is a key cell cycle regulator that acts as a growth factor sensor to integrate extracellular signals with the cell cycle machinery. The expression status of CCNY in lung cancer and its clinical significance remain unknown. The data indicates that CCNY may be deregulated in non-small cell lung cancer, where it may act to promote cell proliferation. These studies suggest that CCNY may be a candidate biomarker of NSCLC and a possible therapeutic target for lung cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Recently, a study conducted by Sun et al reported that the interaction between CCNY and serine/threonine-protein kinase PFTAIRE-1 (PFTK1) might affect HCC through a non-canonical Wnt signaling pathway [ 28 ]. A further study by Yue et al showed that the expression of CCNY was significantly increased in NSCLC [ 16 ]. A previous study has reported that CCNY can enhance cell proliferation, colony formation, cell progression and tumorigenesis in glioma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study conducted by Sun et al reported that the interaction between CCNY and serine/threonine-protein kinase PFTAIRE-1 (PFTK1) might affect HCC through a non-canonical Wnt signaling pathway [ 28 ]. A further study by Yue et al showed that the expression of CCNY was significantly increased in NSCLC [ 16 ]. A previous study has reported that CCNY can enhance cell proliferation, colony formation, cell progression and tumorigenesis in glioma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still limited studies on the molecular mechanism associated with CCNY expression and HCC, although the relationship between CCNY and other human cancers have been studied [ 14 17 ]. Recent studies have shown that CCNY expression is associated with increased cell proliferation in human non small-cell lung cancer (NSCLC), and serum levels of anti-CCNY antibodies are increased in patients with NSCLC when compared with normal controls [ 14 , 16 , 17 ]. Expression of CCNY has also been shown to be increased in human colorectal carcinoma cell lines derived from metastatic carcinoma when compared with cell lines derived from non-metastatic colorectal carcinoma, suggesting a possible role of CCNY in tumor invasion and metastasis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have described how cyclins A, B, D, and E and their respective autoantibodies are overexpressed in various cancers, including lung cancer [14, 1621]. Although CCNY was identified as a novel member of the cyclin family, almost nothing is known about the clinical value of the CCNY protein and anti-CCNY autoantibodies, and only a few studies have reported that the levels of mRNA for CCNY are upregulated in glioma cells and NSCLC tissues [11, 12, 22]. In the present study, we initially used immunohistochemistry to measure the expression levels of CCNY protein in 39 pairs of NSCLC tissues and paratumorous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CCNY protein may play an important role in cancer cell proliferation and metastasis 21,22. Our previous study have shown that CCNY protein is overexpressed in NSCLC tissues 25.…”
Section: Discussionmentioning
confidence: 90%
“…CCNY acts as a growth factor sensor to integrate extracellular signals within the cell cycle machinery 1518. Recent studies have shown that CCNY may play an important role in cancer cell proliferation and metastasis, including breast cancer,19 ovarian cancer,20 lung cancer,21,22 colon cancer,23 glioma,24 etc. We previously found that CCNY mRNA was overexpressed in numerous lung cancer cell lines,21 and that the level of CCNY protein was significantly increased in lung cancer tissues 25.…”
Section: Introductionmentioning
confidence: 99%